Budiman Mahallah kitchen - Ahmad Dahlan, Abdul Rahman; Alias, Majdan; Ibrahim, Jamaludin; Ahmad H.Osman, Rahmah; Mhd. Sarif, Suhaimi; Jaapar, Ghazali; Man, Saupi; Abdul Razak, Dzuljastri; Mohd Ali, Noor Azian; Mohamadali, Noor Azizah; Abdul Aziz, Normaziah; Mahri, Nurhafizah; et al. (mKitchen, 2021)
This book narrates budiman journey in Mahallah Kitchen. Budiman Mahallah Kitchen who are searching for adab (virtue), budi (kindness) and sejahtera (peace). By doing so, budiman and budiwati will have the capacity of bijak berbudi (wisdom in kindness), berani (brave) and bijaksana (full with wisdom). Budiman and budiwati with these attributes will manifest budi bahasa (rasa), budi pekerti (rupa), and budi bicara (roh).